THE STUDY OF ACCEPTING ELECTRONIC MONEY TECHNOLOGY IN LUBUKLINGGAU SOCIETY - Nopalia Nopalia; Dedy Syamsuar (Jurnal TAM (Technology Acceptance Model), 2020)
Computer based technology continuely grow affecting people way of life. One of them is how people counduct daily transaction. Traditioanally, people pay using cash money for their transaction, but recent way, people use cashless to do so using e-money. The aims of this study is to analyse people’s intention and behaviour in utilizing e-money for their payment method. The research deploys the UTAUT model as the basis of the theory. Therefore, the variables used in this study are performance expectancy (PE), Effort expectancy (EE), Social influence (SI), Facilitating condition (FC), Hedonic motivation (HM), Price value (PV), Habit (H), Behavioral Intention (BI) and use behaviour (UB). There are 200 valid responses and then it analyzed by using SEM-PLS. The results of this study indicate that  hedonic motivation (2.193), habit (2,069), facilitating condition (2,841), Price value (0,404) are significantly influence behaviour intention to use e-money but effort expectancy (0,656), Performance expectancy (0,773), and social influence (0,504)not significantly influence behaviour intention. And then Habit (2,501), Facilitating condition (2,501) are significantly influence use behaviour, but behavioral intention (1,011), not significant influence use behaviour  to use e-money.